1994
DOI: 10.1071/eg994019
|View full text |Cite
|
Sign up to set email alerts
|

Precambrian Tasmania: a Thin-skinned Devil

Abstract: An interpretation of geological and geophysical data is presented to suggest that the Precambrian rocks of Tasmania comprise a series of Palaeozoic thrust slices embedded in the western part of the Lachlan Fold Belt and the eastern part of the Kanmantoo Fold Belt. This interpretation contrasts with previous interpretations which regarded the Precambrian rocks as the basement on which the Palaeozoic rocks formed.In western Tasmania, east-or west-facing thrusts and involving detached Precambrian blocks occur in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Some or all of the inliers may be allochthonous terranes that accreted onto the Tasman Fold Belt in the Early Palaeozoic (Leaman 1992; Powell 1992; Elliott et al . 1993; Leaman et al . 1994).…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Some or all of the inliers may be allochthonous terranes that accreted onto the Tasman Fold Belt in the Early Palaeozoic (Leaman 1992; Powell 1992; Elliott et al . 1993; Leaman et al . 1994).…”
Section: Geological Settingmentioning
confidence: 99%
“…In Tasmania there are a number of spatially or structurally separated Proterozoic inliers (or terranes), many of which have been suggested to be allochthonous blocks (Leaman 1992; Powell 1992; Elliott et al . 1993; Leaman et al . 1994; Meffre et al .…”
Section: Introductionmentioning
confidence: 99%
“…A diverse range of techniques have so far been exploited to infer information on crustal structure and composition beneath Bass Strait, mainly in studies focusing on similarities recognised in the geology (Crawford and Berry, 1992;Powell and Baillie, 1992;Reed, 2001;Cayley, 2011) and in geophysical, geochemical and other types of data in Tasmania and/or mainland Australia. Geophysical methods include potential field imaging and modelling (e.g., Leaman et al, 1994;Gunn et al, 1997aGunn et al, , 1997bMorse et al, 2009;McLean et al, 2010), seismic reflection profiling (Drummond et al, 2000;Cayley et al, 2011) and seismic tomography (Rawlinson and Kennett, 2008). Palaeomagnetic evidence in the form of magnetic remanence (Li et al, 1997) has also been used.…”
Section: Introductionmentioning
confidence: 99%
“…More than two decades ago it was postulated that the Tamar River marks the approximate location of a crustal‐scale suture zone [ Williams , 1989] ‐ sometimes referred to as the Tamar Fracture System ‐ between ETT and WTT. This idea has since been questioned [ Leaman et al , 1994; Reed , 2001; Rawlinson et al , 2010], and the observed changes in stratigraphy that gave rise to the original hypothesis are now interpreted as being related to thin‐skinned (near‐surface) tectonic processes [ Leaman et al , 1994].…”
Section: Introductionmentioning
confidence: 99%